Comparative effect of dose escalation of nanocapsulated ivermectin against mange in rabbits - Azza Abdelmoteleb; Dalia Elmasry; Fatma Amro; Reham Mahmoud (German Journal of Veterinary Research)
The present study aimed to investigate the effects of nano-capsulated ivermectin on the liver and kidney function and oxidative status in mite infested-rabbits, compared to ivermectin. Additionally, the ivermectin residue profile in adipose tissue, liver, muscle, and kidney was evaluated. For this purpose, nano-capsulated ivermectin was prepared and characterized using high-resolution transmission electron microscopy (HRTEM) and cytotoxicity assay on Vero cells. To assess the effect of dose escalation of nano-capsulated ivermectin, one-hundred naturally mite-infested male rabbits were divided into four groups (G1-G4; n=25). Rabbits kept in G1 were left untreated (positive control), while rabbits kept in G2 and G3 received subcutaneously 200 and 400 μg/kg body weight ivermectin, respectively, at zero-day and repeated after two weeks of the first injection. Rabbits in G4 were treated with 200 μg/kg nano-capsulated ivermectin at zero day as a single dose. Additionally, twenty-five healthy male rabbits (G0) were used as a negative control. The efficacy was assessed based on clinical manifestations, liver and kidney function, and oxidative stress parameters. Ivermectin residues were measured in fat, liver, muscle, and kidney using high-performance liquid chromatography (HPLC). Results showed that the size of the nano-capsulated ivermectin was 35.4 nm with a narrow size distribution of 0.578 polydispersity indexes. A significant improvement in liver and kidney functions (P